Impact of depth of invasion on local recurrence in R0 resected node‐negative oral tongue squamous cell carcinoma. Issue 3 (13th December 2022) - Dang, Rushil R.; Kim, Jaegak; Qureshi, Muhammad M.; Fazeli, Shoreh Roghayeh; Zhao, Qing; Noonan, Vikki L.; Sundararajan, Devaki; Salama, Andrew; Truong, Minh Tam
Abstract: Background: This study evaluates the impact of depth of invasion (DOI) on local recurrence (LR) in node‐negative oral tongue squamous cell carcinoma (SCC). Methods: Fifty‐one patients were retrospectively reviewed from an institutional database. Patients were evaluated for local control (LC). Cox‐proportional hazards modeling was used to calculate hazard ratios. Results: There were 84.3% T1/2 and 15.7% T3/4 classification tumors. The 3‐year overall survival rate was 97.9%. Local failure rate was 5.7% with a 3‐year LC of 93.6%. On Univariate analysis, increased hazard of LR was noted with each unit increase in DOI (HR 1.40, 95% CI 1.07–1.83, p  = 0.014). Age, sex, T classification, margins ≥5 mm, lymphovascular invasion (LVI) and perineural invasion (PNI), and adjuvant treatment were not associated with LR. On Multivariate analysis, adjusting for age and adjuvant treatment, results for DOI remained significant (aHR 1.46, 95% CI 1.08–1.98, p  = 0.013). Conclusion: On evaluation of our institutional dataset increasing DOI was associated with increased hazard of local recurrence with oral tongue SCC.